2019
DOI: 10.3390/magnetochemistry5020031
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Conflicts of Interest and Misleading Statements in Official Reports about the Health Consequences of Radiofrequency Radiation and Some New Measurements of Exposure Levels

Abstract: Official reports to governments throughout the Western world attempt to allay public concern about the increasing inescapability of the microwaves (also known as radiofrequency radiation or RF) emitted by “smart” technologies, by repeating the dogma that the only proven biological effect of RF is acute tissue heating, and assuring us that the levels of radiation to which the public are exposed are significantly less than those needed to cause acute tissue heating. The present paper first shows the origin of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The article [1] in Magnetochemistry will be marked as retracted. The Editorial Board have re-examined the paper post-publication and found that it contains no scientific contribution and that Magnetochemistry is not the appropriate forum for this kind of "opinion" publication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The article [1] in Magnetochemistry will be marked as retracted. The Editorial Board have re-examined the paper post-publication and found that it contains no scientific contribution and that Magnetochemistry is not the appropriate forum for this kind of "opinion" publication.…”
mentioning
confidence: 99%
“…MDPI is a member of the Committee on Publication Ethics and takes the responsibility to enforce strict ethical policies and standards very seriously. To ensure the addition of only high-quality scientific works to the field of scholarly publication, [1] is retracted and shall be marked accordingly. We apologize to the readership of Magnetochemistry for any inconvenience caused.…”
mentioning
confidence: 99%
“…A study measured the microwave leakage of 106 microwave ovens and found that only one oven exceeded the 5 mW/cm 2 emission limit (9). Though generally considered as safe when used properly, there are some arguments that microwave exposure at much lower levels could be associated with adverse health effects (5,10).…”
mentioning
confidence: 99%